Beyond the DSM story ethical quandaries, challenges, and best practices - Eriksen, Karen, 1956-; Kress, Victoria E.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2005)
Challenges the 'Diagnostic & Statistical Manual' system from ethical & cultural perspectives, with a critical evaluation of how it fits with other professional & theoretical orientations.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Diagnostic and statistical manual of mental disorders -- Evaluation; Mental illness -- Diagnosis; Mental illness -- Classification; Electronic books